'Flexible' caste boundaries: cross-regional marriage as mixed marriage in rural north India. Issue 2 (3rd April 2019) - Chaudhry, Shruti
ABSTRACT: Based on ethnographic fieldwork in a village in the north Indian state of Uttar Pradesh, this article focuses on cross-regional marriage (those that cross caste and linguistic boundaries and entail long-distance migration) as mixed marriage. It queries the 'acceptance' of women sought beyond traditional boundaries of caste in a context where caste endogamy is the norm and breaches are otherwise not tolerated. It argues that while the caste of the women is overlooked when the alliance is made, their caste does not cease to be a concern in the caste-bound rural communities into which they marry. A discourse of caste, centred on food transactions, derogatory remarks about skin colour and in the refusal to marry the children of cross-regional couples, serves to mark difference and make claims to status. While there has been a decline in certain exclusionary caste practices in the village, a sense of hierarchy is retained.